Improved hypertension control at six months using an adapted WHO HEARTS-based implementation strategy at a large urban HIV clinic in Uganda - Martin Muddu; Fred C. Semitala; Isaac Kimera; Mary Mbuliro; Rebecca Ssennyonjo; Simon P. Kigozi; Rodgers Katwesigye; Florence Ayebare; Christabellah Namugenyi; Frank Mugabe; Gerald Mutungi; Chris T. Longenecker; et al. (BMC, 2022)
Abstract Objectives To adapt a World Health Organization HEARTS-based implementation strategy for hypertension (HTN) control at a large urban HIV clinic in Uganda and determine six-month HTN and HIV outcomes among a cohort of adult persons living with HIV (PLHIV). Methods Our implementation strategy included six elements: health education, medication adherence, and lifestyle counseling; routine HTN screening; task shifting of HTN treatment; evidence-based HTN treatment protocol; consistent supply of HTN medicines free to patients; and inclusion of HTN-specific monitoring and evaluation tools. We conducted a pre-post study from October 2019 to March 2020 to determine the effect of this strategy on HTN and HIV outcomes at baseline and six months. Our cohort comprised adult PLHIV diagnosed with HTN who made at least one clinic visit within two months prior to study onset. Findings We enrolled 1,015 hypertensive PLHIV. The mean age was 50.1 ± 9.5 years and 62.6% were female. HTN outcomes improved between baseline and six months: mean systolic BP (154.3 ± 20.0 to 132.3 ± 13.8 mmHg, p < 0.001); mean diastolic BP (97.7 ± 13.1 to 85.3 ± 9.5 mmHg, p < 0.001) and proportion of patients with controlled HTN (9.3% to 74.1%, p < 0.001). The HTN care cascade also improved: treatment initiation (13.4% to 100%), retention in care (16.2% to 98.5%), monitoring (16.2% to 98.5%), and BP control among those initiated on HTN treatment (2.2% to 75.2%). HIV cascade steps remained high (> 95% at baseline and six months) and viral suppression was unchanged (98.7% to 99.2%, p = 0.712). Taking ART for more than two years and HIV viral suppression were independent predictors of HTN control at six months. Conclusions A HEARTS-based implementation strategy at a large, urban HIV center facilitates integration of HTN and HIV care and improves HTN outcomes while sustaining HIV control. Further implementation research is needed to study HTN/HIV integration in varied clinical settings among diverse populations.